Quality of Broiler Chicken Carcass Given Katuk Leaf Flour (Sauropus androgynus) in Feed - Agustama, Chandra; Windyasmara, Ludfia; Sukaryani, Sri (Universitas Veteran Bangun Nusantara, 2024)
Broiler chickens are the result of crossing several breeds which are very productive, especially in the production of chicken meat. Market and public demand for broiler chickens for consumption is also very high. However, consumers are now increasingly smart in choosing animal products with excellent carcass quality. Adding katuk (Sauropus androgynus) leaf flour to feed can be an alternative to improving broiler carcass quality because katuk (Sauropus androgynus) leaf flour contains phytochemical compounds such as: saponins, tannins and B-carotene. This study aims to determine the effect of katuk (Sauropus androgynus) leaf flour supplementation on broiler chicken carcass quality. This research used a Completely Randomized Design (CRD) with a unidirectional pattern with a rearing period of 28 days with 4 treatments and 3 repetitions, namely P0: Giving 100% base feed without any additions, P1: Giving 100% base feed + (1%) katuk leaf flour , P2: Feeding 100% alkaline + (3%) katuk leaf flour, P3: Feeding 100% alkaline + (5%) katuk leaf flour. The variables observed included: carcass percentage, non-carcass percentage, and abdominal fat percentage. Research data was analyzed using Analysis of Variance (ANOVA), followed by the Duncan Multiple Range Test (DMRT). The research results showed the addition of katuk leaf flour with treatments of 0%, 1%, 3%, 5%. The addition of katuk leaf flour to feed can reduce the abdominal fat rate of broiler chickens, but does not affect the carcass rate and non-carcass rate of broiler chickens. P3 treatment with the addition of 5% katuk leaf flour to the feed had the effect of reducing the percentage of abdominal fat.